1987
DOI: 10.1038/eye.1987.12
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and surgical management of acquired bilateral superior oblique palsy

Abstract: Thirty-four patients with surgically treated bilateral superior oblique palsy are presented. The patients are divided into three groups: Symmetrical palsies, Asymmetrical palsies, A group in whom the bilaterality was initially masked. Bilaterality should be suspected in all cases of traumatic IVth nerve paresis, and particularly in cases with a large 'V' pattern, excyclo deviation of more than 10 degrees on down-gaze and when right hypertropia switches to left hypertropia on lateral down-gaze. Bilateral Harada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…8,9 This is largely due to a significant increase in excyclotropia in downgaze, as demonstrated in studies by Kraft and coworkers 10 and Georgievski and Kowal, 11 the latter measuring an increase in the mean excyclotropia from primary position to downgaze of 6% and 106% in patients with unilateral and bilateral superior oblique palsy, respectively.…”
mentioning
confidence: 87%
“…8,9 This is largely due to a significant increase in excyclotropia in downgaze, as demonstrated in studies by Kraft and coworkers 10 and Georgievski and Kowal, 11 the latter measuring an increase in the mean excyclotropia from primary position to downgaze of 6% and 106% in patients with unilateral and bilateral superior oblique palsy, respectively.…”
mentioning
confidence: 87%
“…Fells and his team 13 reviewed the management of bilateral superior oblique palsy and stressed the importance of dealing with any significant torsion as a primary procedure, using his modification of the Harada Ito procedure. Failure to deal with the torsion was an important barrier to a satisfactory fusion result in this series.…”
Section: Introductionmentioning
confidence: 99%
“…Price et al (1987), reviewing their series of acquired bilateral superior oblique palsy, concluded that about 38% were initially masked. Price et al (1987), reviewing their series of acquired bilateral superior oblique palsy, concluded that about 38% were initially masked.…”
Section: Featuresmentioning
confidence: 99%